FAKTOR YANG MEMPENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR DI BEI - SHERLLY TJOKRO; Debora Debora (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to provide empirical evidence that profit and loss, audit opinion, size KAP, audit committee, firm size, profitability, solvency have an effect on audit report lag. This study uses data taken from manufacturing companies that are consistently listed on the Indonesia Stock Exchange during the period 2017 to 2019. Sampling uses the purposive sampling method. The sample of this study amounted to 300 companies that meet the criteria. This study uses multiple regression analysis. The result of this research show that variable auditor’s opinion, profitability had negative influence toward audit report lag, while variable profit and loss, size of KAP, audit committe, firm size and solvency had no influence toward audit report lag.